(untitled) (Research, Society and Development, 2022)
The role of regular physical exercise is recognized for the prevention, control and treatment of cardiovascular diseases. However, studies show that after strenuous aerobic exercise sessions in healthy individuals can lead to cardiac damage, due to the high degree of stress imposed on myocardial structures. This study verifies the effects of swimming to exhaustion on contraction and relaxation velocities, as well as the velocity of calcium release and reuptake in cardiomyocytes isolated from the left ventricle. Wistar animals aged 16 weeks were submitted to a protocol of swimming until exhaustion with a load of 5% of body weight and later the cardiomyocytes were isolated. It was observed that an acute session of swimming until exhaustion promoted an increase in the velocity of contraction and relaxation and an increase in the velocity of calcium release. Exercise to exhaustion promotes adverse effects on the myocardium, however more studies are needed to explain these effects and demonstrate the molecular mechanisms involved in the process.